Strategi Komunikasi Untuk Mensosialisasikan Program Harmonisasi Kebijakan di BRI - Amrina, Afrilla; Naryoso, Agus; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Policies implemented without proper governance and communication strategies often lead to misunderstandings or miscommunications. PT Bank Rakyat Indonesia (Persero) Tbk. has implemented a policy harmonization program aimed at aligning its various policies. This study 1 investigates the internal communication strategy employed by BRI to socialize this program, using the Cultip Center Communication Planning Model as a framework. A qualitative descriptive research method was used, with in-depth interviews as the primary data collection technique. Findings reveal that BRI's policy harmonization program was implemented through four key stages: fact-finding, planning, communicating, and evaluating.